EFEKTIFITAS PEER GROUP EDUCATION TENTANG GIZI SEIMBANG TERHADAP PERILAKU GIZI PADA ANAK USIA SEKOLAH - Nur Hidayati, Rina; Ibnu, Faisal (JURNAL KEPERAWATAN BINA SEHAT, 2014)
The behavior of children who do not eat well result in school-age children at risk for nutritional problems either undernutrition or over nutrition. The habit of unhealthy food consumption is more influenced by peers. Empowerment through peer group education in providing peer education in schools is more practical for school-age children, because the peer group provides a stronger influence on the adoption of healthy behaviors children. The purpose of this study is the identification of the effectiveness of peer group education about behavior nutrition balanced for school-age childrens. This research used a design of experiments, conducted in December 2013 - November 2014. The population of the research is the entire school-age children in grades 4-6 with MI Nurul Huda Miji Mojokerto totaling 50 people, using total sampling. In the control group was given a balanced nutrition booklet with self-learning, while the case is given peer group education activities for 8 weeks. The results showed is difference in the nutritional behavior of children, especially in the case group before and after the given peer group education that an increase in well nutritional behavior well as much as 50%. Peer group education proved to be effective in improving childrens well nutrition behavior as much as 64%.. Peer group education can be used as a nursing intervention strategies are effective in changing childrens well behavior nutrition.Keywords: Peer Group Education, Balanced Nutrition, School Age Children